(untitled) (Research, Society and Development, 2022)
Objectives: To assess psychological repercussions and the perception to act in patient care in the Covid-19 pandemic among medical students in Fortaleza-CE, Brazil. Methodology: This was a cross-sectional, analytical study from December 2020 to February 2021. Participants were pre-internship and internship medical students from three Brazilian medical schools and voluntarily completed an online questionnaire about sociodemographic data, perceived risk for the COVID-19 pandemic, and post-traumatic stress symptoms assessed by the Impact of Event Scale (IES) in its Brazilian version. All of them signed an informed consent form, and the study was approved by the Ethics and Research Committee of the institutions. Spearman and Kruskal Wallis tests were used to compare the groups, with alpha error lower than 5%. Results: There were 94 participants, 60.6% female, 86.2% from private universities. 53.3% had a perception of high risk of infection with the virus and 40.2% reported unsatisfactory sleep quality. The mean IES score of the participants was 14.8 +/- 5.78, showing that there was a stressful impact. There was statistical significance related to the IES scores when assessing risk of infection, sleep, university, and psychological follow-up. Conclusion: The Covid-19 pandemic generated a stressful impact on the medical students evaluated, with importance for future psychological interventions in times of pandemics.